StartLink and StartLink+: Prediction of Gene Starts in Prokaryotic Genomes - Gemayel, Karl; Lomsadze, Alexandre; Borodovsky, Mark (Frontiers in Bioinformatics, 2021)
State-of-the-art algorithms of ab initio gene prediction for prokaryotic genomes were shown to be sufficiently accurate. A pair of algorithms would agree on predictions of gene 3’ends. Nonetheless, predictions of gene starts would not match for 15-25% of genes in a genome. This discrepancy is a serious issue that is difficult to resolve due to the absence of sufficiently large sets of genes with experimentally verified starts. We have introduced StartLink that infers gene starts from conservation patterns revealed by multiple alignments of homologous nucleotide sequences. We also have introduced StartLink+ combining both ab initio and alignment-based methods. StartLink ability to predict a start of given gene is restricted by availability of homologs in a database. We observed that StartLink made predictions for 85% of genes per genome on average. The StartLink+ accuracy was shown to be 98-99% on the sets of genes with experimentally verified starts. In comparison with database annotations, we observed that the annotated gene starts deviated from the StartLink+ predictions for ~5% of genes in AT-rich genomes and for 10-15% of genes in GC-rich genomes on average. Use of StartLink+ has a potential to significantly improve gene start annotation in genomic databases.